Zika Virus Induces Sex-Dependent Metabolic Changes in Drosophila melanogaster to Promote Viral Replication - Tafesh-Edwards, Ghada; Kalukin, Ananda; Eleftherianos, Ioannis (Frontiers in Immunology, 2022)
Zika is a member of the Flaviviridae virus family that poses some of the most significant global health risks, causing neurologic complications that range from sensory neuropathy and seizures to congenital Zika syndrome (microcephaly) in infants born to mothers infected during pregnancy. The recent outbreak of Zika virus (ZIKV) and its serious health threats calls for the characterization and understanding of Zika pathogenesis, as well as host antiviral immune functions. Although ZIKV has been associated with activating the RNA interference (RNAi) immune pathway and altering host metabolism, in-depth studies are still required to uncover the specifics of the complex host-virus interactions and provide additional insights into the molecular components that determine the outcome of this disease. Previous research establishes the fruit fly Drosophila melanogaster as a reliable model for studying viral pathogens, as it shares significant similarities with that of vertebrate animal systems. Here, we have developed an in vivo Drosophila model to investigate ZIKV-mediated perturbed metabolism in correlation to the RNAi central mediator Dicer-2. We report that ZIKV infection reprograms glucose and glycogen metabolism in Dicer-2 mutants to maintain efficient replication and successful propagation. Flies that exhibit these metabolic effects also show reduced food intake, which highlights the complicated neurological defects associated with ZIKV. We show that ZIKV infection significantly reduces insulin gene expression in Dicer-2 mutants, suggesting an insulin antiviral role against ZIKV and a direct connection to RNAi immunity. Moreover, we find that the insulin receptor substrate chico is crucial to the survival of ZIKV-infected flies. These observations are remarkably more severe in adult female flies compared to males, indicating possible sex differences in the rates of infection and susceptibility to the development of disease. Such findings not only demonstrate that metabolic alterations can be potentially exploited for developing immune therapeutic strategies but also that preventive measures for disease development may require sex-specific approaches. Therefore, further studies are urgently needed to explore the molecular factors that could be considered as targets to inhibit ZIKV manipulation of host cell metabolism in females and males.